Assessment of the Periodontal Health and Community Periodontal Index in Serbian Military - Kovačević, Vladan; Milosavljević, Marko; Rančić, Nemanja; Daković, Dragana (Vojnosanitetski pregled, 2015)
Background/Aim: The aim of study was to assess the periodontal condition in Serbian military population using the community periodontal index of treatment needs (CPITN), and the influence of general life habits and local risk factors on periodontal health. Methods: Prospective cross-sectional pilot study was conducted on 101 examinees at mean age of 38.94±11.63 years who had dental check ups at the Dental Clinic of the Military Medical Academy. All categories of military personnel aged 20-64 years were divided into five groups. The frequency distribution of general and local factors on periodontal health, oral hygiene index, and the assessment of mean number of sextants by CPITN index compared to the age were examined. Results: The examinees at age of 51-60 years had the best oral hygiene (0.95±0.65), whereas the oldest population had the worst (1.63±0.42). Only one person at the age group of 51-60 years had completely healthy periodontium (5.6%). Observed in relation to the age groups, the mean values of sextants increased linearly, but in general population, the most frequent CPITN categories were in sextant with the periodontal pockets 4-5 mm (score 3). Conclusions: Compared to the results from other countries shown by the World Health Organization, the periodontal condition in our examinees is below the average. The appropriate preventive program preparation and implementation are needed, including primarily the appropriate training on oral hygiene, as well as education based on periodontal disease prevention and development.